Mengkomunikasikan Pendidikan Literasi Iklan untuk Anak - Juni Alfiah Chusjairi (Departement of Mathematics Education, 2023)
This article is a review of studies on advertising literacy for children. Advertising literacy is the ability to understand and interpret an advertisement. This ability is certainly needed for children considering that advertising is no longer only in traditional media such as television but also in contemporary media which children may use every day. Like in the games on their devices. Advertising literacy studies are still rare in Indonesia, so it is necessary to look at past studies to get an idea of ​​what can be done when conducting studies in this area. Several concepts, examples and experimental methods were carried out for advertising literacy studies as described in this paper.